Exploring Policies to Reduce Stunting in Indonesia, Philippines, Malaysia, and Vietnam: A Literature Review - Handika, Yola Rezki; Laila, Elvi Nur Nujumul; Maulana, Muhammad Iqbal; Aminan, Muhammad Haris; Negoro, Abul Haris Suryo (Universitas Muhammadiyah Ponorogo, 2025)
Stunting is a global problem that occurs in developing countries. Stunting policies in developing countries have different implementation trends.Â This research aims to explore and describe stunting policies through Indonesian government programs with the governments of the Philippines, Malaysia, and Vietnam. The selection of country objects is determined based on the average stunting prevalence rate based on the Asian Development Bank in 2022, namely 2 countries above the average stunting prevalence in Southeast Asia (Indonesia and the Philippines) and 2 countries below the average stunting prevalence rate (Vietnam and Malaysia). This research was conducted using a literature study method on 80 main articles from international journals with a publication range of 2019-2024.Â The findings were analyzed with indicators of successful policy implementation: Communication, Resources, Disposition, and Bureaucratic Structure which serve to assess the role and success of the policy. This research shows that there are similarities and differences in the policy implementation framework in each country. Similarities are caused by culture, socio-demographics, and poverty which are the dominant factors for stunting. The differences that arise are caused by the approach chosen by the government to overcome stunting. As a recommendation, the government needs to make the stunting handling program a national priority. In supporting the success of stunting management policies, it is necessary to strengthen coordination between institutions, build commitment between implementers, and align the policy agenda between stakeholders